Regional contributions of D-serine to Alzheimer’s disease pathology in male AppNL–G–F/NL–G–F mice - Ni, Xiance; Inoue, Ran; Wu, Yi; Yoshida, Tomoyuki; Yaku, Keisuke; Nakagawa, Takashi; Saito, Takashi; Saido, Takaomi C.; Takao, Keizo; Mori, Hisashi (Frontiers in Aging Neuroscience, 2023)
Background Neurodegenerative processes in Alzheimer’s disease (AD) are associated with excitotoxicity mediated by the N-methyl-D-aspartate receptor (NMDAR). D-Serine is an endogenous co-agonist necessary for NMDAR-mediated excitotoxicity. In the mammalian brain, it is produced by serine racemase (SRR) from L-serine, suggesting that dysregulation of L-serine, D-serine, or SRR may contribute to AD pathogenesis. Objective and methods We examined the contributions of D-serine to AD pathology in the AppNL–G–F/NL–G–F gene knock-in (APPKI) mouse model of AD. We first examined brain SRR expression levels and neuropathology in APPKI mice and then assessed the effects of long-term D-serine supplementation in drinking water on neurodegeneration. To further confirm the involvement of endogenous D-serine in AD progression, we generated Srr gene-deleted APPKI (APPKI-SRRKO) mice. Finally, to examine the levels of brain amino acids, we conducted liquid chromatography–tandem mass spectrometry. Results Expression of SRR was markedly reduced in the retrosplenial cortex (RSC) of APPKI mice at 12 months of age compared with age-matched wild-type mice. Neuronal density was decreased in the hippocampal CA1 region but not altered significantly in the RSC. D-Serine supplementation exacerbated neuronal loss in the hippocampal CA1 of APPKI mice, while APPKI-SRRKO mice exhibited attenuated astrogliosis and reduced neuronal death in the hippocampal CA1 compared with APPKI mice. Furthermore, APPKI mice demonstrated marked abnormalities in the cortical amino acid levels that were partially reversed in APPKI-SRRKO mice. Conclusion These findings suggest that D-serine participates in the regional neurodegenerative process in the hippocampal CA1 during the amyloid pathology of AD and that reducing brain D-serine can partially attenuate neuronal loss and reactive astrogliosis. Therefore, regulating SRR could be an effective strategy to mitigate NMDAR-dependent neurodegeneration during AD progression.